The MATH COMICS TO IMPROVE MATHEMATICAL COMMUNICATION SKILLS - Samara Alifa Jazuli; Syafmen, Wardi; Falani, Ilham (Universitas Muhammadiyah Metro, 2024)
This research and development aims to determine the quality of mathematical comics using the PBL model in improving students' mathematical communication skills in terms of validity, practicality and effectiveness. The method used in this research is Research and Development using the ADDIE model (Analysis, Design, Development, Implementation and Evaluation). The results obtained in this research were that the material validation percentage was 82.6% in the